MiRNA-21 Reverses High Glucose and High Insulin Induced Insulin Resistance in 3T3-L1 Adipocytes through Targeting Phosphatase and Tensin Homologue - Ling, H.-y.; Hu, B.; Hu, X.-b.; Zhong, J.; Feng, S.-d.; Qin, L.; Liu, G.; Wen, G.-b.; Liao, D.-f. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Our previous study showed there was a change of microRNA (miRNA) expression profile, and miR-21 was significantly down regulated in insulin-resistant adipocytes (IR-adipocytes). Phosphatase and tensin homologs deleted on chromosome 10 (PTEN), a negative regulator of the phosphatidylinositol 3-kinase (PI3K)/AKT pathway, was identified to be a target gene of miR-21, which suggested miR-21 might be associated with insulin resistance (IR) or diabetes. However, it is not known whether miR-21 play any role in the development of IR in 3T3-L1 adipocytes.Normal adipocytes and adipocytes transfected with pre-miR-21(pmiR-21) or negative control (pNeg) were treated with high glucose and high insulin for 24 h, insulin-stimulated glucose uptake was determined by 2-Deoxyglucose transport assay, miR-21 expression level was measured by using quantitative real-time RT-PCR (qRT-PCR). The protein expression levels of PTEN, Akt, phospho-Akt (Ser473), IRβ, GSK3β, phospho-GSK3β (Ser9) and GLUT4 were detected by western blotting assay.We further confirmed that miR-21 was down regulated in IR-adipocytes by qRT-PCR. Over-expression of miR-21 significantly increased insulin-induced glucose uptake and decreased PTEN protein expression, while it had no significant effect on PTEN mRNA expression in IR-adipocytes. Moreover, over-expressing miR-21 significantly increased insulin-induced phosphorylation of AKT (Ser473), GSK3β (Ser9) and the translocation of glucose transporter 4 (GLUT4) in IR-adipocytes.In this study, our data demonstrate that miR-21 reverses high glucose and high insulin induced IR in 3T3-L1 adipocytes, possibly through modulating the PTEN-AKT pathway, and miR-21 may be a new therapeutic target for metabolic diseases such as T2DM and obesity.
Keywords: miR-21; insulin resistance; PTEN; AKT